Exosomes derived from ccRCC cells confers fibroblasts activation to foster tumor progression through Warburg effect by downregulating PANK3 - Yang Yang; Cheng Qiang; Zhu Jie; Han Ce; Huang Yan; Li Xiu-bin; Fan Wen-mei; Zhang Xu; Gao Yu (Cell Death Discovery)
Abstract The interaction between tumor-derived exosomes and stroma plays a crucial role in tumor progression. However, the mechanisms through which tumor cells influence stromal changes are not yet fully understood. In our study, through single-cell sequencing analysis of clear cell renal cell carcinoma tissues at varying stages of progression, we determined that the proportion of cancer-associated fibroblasts (CAFs) in advanced renal cell carcinoma tissues was notably higher compared to localized renal cell carcinoma tissues. Comparison of transcriptome sequencing and energy metabolism tests between CAFs primarily isolated from advanced renal cell carcinoma tissues and normal fibroblasts (NFs) revealed the occurrence of the Warburg effect during the fibroblast activation process. Additionally, we observed an increase in glucose transporter GLUT1 expression, total reactive oxygen species (ROS) levels, lactic acid production, and subsequent excretion of excess lactic acid through monocarboxylate transporter-4 (MCT4) in CAFs. Interestingly, renal cancer cells were found to uptake lactic acid via MCT1 upon interaction with CAFs, thereby enhancing their malignant phenotypes. Furthermore, the down-regulation of PANK3 induced by exosomes derived from renal cancer cells was identified as a crucial step in fibroblast activation. These findings indicate that exosomes play a role in facilitating intercellular communication between renal cancer cells and fibroblasts. Targeting this communication pathway could potentially offer new strategies for the prevention and treatment of advanced renal cell carcinoma.